Current applications of poly(lactic acid) composites in tissue engineering and drug delivery - Liu, Shan; Qin, Shuhao; He, Min; Zhou, Dengfeng; Qin, Qingdong; Wang, Hao (Composites. Part B, Engineering, 2020)
Biodegradable poly(lactic acid) (PLA) presents suitable physicochemical properties and biocompatibility for biomedical engineering. However, PLA has some drawbacks, such as low cell adhesion, biological inertness, low degradation rate, and acid degradation by-products. In this review, recent progress on strategies to address these problems is summarized, including novel fabrication techniques, high-performance PLA composites, and their applications for tissue engineering and drug delivery. The scaffolds, especially for bone regeneration, blood vessels, organs, and skin regeneration are evaluated, in terms of in vivo and in vitro biocompatibility and biodegradability. The enhanced mechanical, thermal, and rheological properties of PLA biocomposites are analyzed in detail. PLA biocomposites for drug encapsulation, sustained release, and tumor-targeting are also reviewed. Furthermore, the challenges and future perspectives on PLA-based biocomposites are discussed.